FOXP3 suppresses breast cancer metastasis through downregulation of CD44. Issue 6 (25th February 2015) - Zhang, Cun; Xu, Yujin; Hao, Qiang; Wang, Shuning; Li, Hong; Li, Jialin; Gao, Yuan; Li, Meng; Li, Weina; Xue, Xiaochang; Wu, Shouzhen; Zhang, Yingqi; et al.
<x xml:space="preserve">Abstract</x> Forkhead box protein 3 (FOXP3) plays an important role in breast cancer as an X‐linked tumor suppressor gene. However, the biological functions and significance of FOXP3 in breast cancer metastasis remain unclear. Here, we find that, clinically, nuclear FOXP3 expression is inversely correlated with breast cancer metastasis. Moreover, we demonstrate that FOXP3 significantly inhibits adhesion, invasion and metastasis of breast cancer cells in vivo and in vitro. In addition, the adhesion molecule CD44 is found to be suppressed by FOXP3 through transcriptome sequence analysis (RNA‐seq). A luciferase reporter assay, chromatin immunoprecipitation and electrophoretic mobility shift assay identify CD44 as a direct target of FOXP3. The expression of CD44 is downregulated by FOXP3 in breast cancer cells. Importantly, anti‐CD44 antibody reverses the FOXP3 siRNA‐induced effects on the breast cancer cells in vitro and FOXP3 expression level in the nucleus of breast cancer cells is inversely correlated with CD44 expression level in clinic breast cancer tissues. Taken together, the results from the present study suggest that FOXP3 is a suppressor of breast cancer metastasis. FOXP3 directly binds to the promoter of CD44 and inhibits its protein expression, thereby suppressing adhesion and invasion of human breast cancer cells. This finding highlights the therapeutic potential of FOXP3‐CD44 signaling to inhibit breast cancer metastasis.